Effects of Anakinra on Health-Related Quality of Life in a Patient with 1129G>A/928G>A Mutations in MVK Gene and Heterozygosity for the Mutation 2107C>A in CIAS1 Gene - Laccetta, Gianluigi; Tutera, Maria; Miccoli, Mario; Consolini, Rita (Frontiers in Pediatrics, 2017)
Mevalonate kinase deficiency impairs several aspects of the patient’s quality of life, thus early diagnosis and treatment are required to improve health related quality of life. A 15-year old patient with double heterozygosity for the mutations 1129G>A and 928G>A in MVK gene, heterozygosity for the mutation 2107C>A in CIAS1 gene and hyper-IgD syndrome phenotype, has been treated with anakinra with a reduction of 50% in the number of fever episodes per month, a reduction of 33% in the days of fever for each attack and normal blood tests in the intercritical phase. The RAND 36-Item Health Survey has been used for the assessment of health related quality of life before and after the treatment with anakinra. The patient’s quality of life showed an overall improvement of 27%; results showed a better improvement in role limitations due to physical health (50%).